REDUCED DNASE ENZYME ACTIVITY IN RESPONSE TO HIGH POST-INJURY MITOCHONDRIAL DNA CONCENTRATION PROVIDES A THERAPEUTIC TARGET FOR SIRS - McIlroy, Daniel J; Minahan, Kyra; Keely, Simon; Lott, Natalie; Hansbro, Philip; Smith, Doug W; Balogh, Zsolt J (The journal of trauma and acute care surgery, 2018)
Cell free mitochondrial DNA (mtDNA) is pro-inflammatory and has been detected in high concentrations in trauma patients' plasma. Deoxyribonuclease (DNase) is the free plasma enzyme responsible for the digestion of extracellular DNA. The relationship between mtDNA and DNase after major trauma is unknown. We hypothesized that DNase activity would be elevated after injury and trauma surgery, and would be associated with high concentrations of extracellular DNA. 2-year prospective study was performed on 103 consecutive trauma patients (Male 81%, Age: 38 IQR 30-59 years; ISS: 18 IQR 12-26) who underwent standardised major orthopaedic trauma surgical interventions. Blood was collected at 5 peri-operative time points (pre-op, post-op, 7hrs, 24hrs and 3 days post-operatively). Healthy control subjects (n=20) were also sampled. Cell free mtDNA and nuclear DNA(nDNA) was measured using quantitative polymerase chain reaction. DNase was also assayed in the same plasma samples. Increased levels of mtDNA (from Pre-op 163±86ng/ml to 3 days 282±201ng/ml p<0.0001) and nDNA (from pre-op 28±20ng/ml to 3 days 37±27ng/ml p<0.05) were present in trauma patients at all peri-operative time points compared to healthy controls (mtDNA: 4±2ng/ml; nDNA: 10±5ng/ml). DNase activity was lower in the trauma cohort (from Pre-op 0.06±0.04U/ml to 3 days 0.08±0.04U/ml p<0.0001) compared to healthy controls (DNase: 0.17±0.03U/ml). There was no correlation between DNase and peri-operative DNA concentrations. Elevated mtDNA (but not nDNA) correlated with the development of SIRS (p=0.026) but not MOF. The significant perioperative elevation in plasma free MtDNA concentration is associated with the development of SIRS. The fact that increased cell free DNA concentrations present with significantly lower than healthy control DNase activity suggests a potential therapeutic opportunity with DNase administration to modulate post-injury severe SIRS LEVEL OF EVIDENCE: Level II: Prospective comparative study.